Peningkatan Hasil Belajar Matematika Materi Pembagian melalui Media Sedotan pada Siswa Kelas III SD Al Islam Yogyakarta - Asvinirmala Fitri Kusuma Mahardhika; Andayani (Kilau Publishing, 2025)
This study was motivated by the low learning outcomes of students in the topic of whole-number division, as indicated by the large number of students who had not achieved learning mastery and their lack of concentration during mathematics lessons. The study aimed to improve the learning outcomes of third-grade students of SD Al Islam Yogyakarta on whole-number division through the use of straws as a teaching aid. This research employed Classroom Action Research conducted in two cycles. The subjects of the study were 15 third-grade students, while the object of the study was students’ mathematics learning outcomes on whole-number division material. Data were collected through formative tests of student learning outcomes. The data were analyzed using descriptive quantitative analysis by comparing the percentage of learning mastery and the mean scores across cycles. The results showed an improvement in student learning outcomes, with the mastery level in Cycle I reaching 66.67% and a mean score of 82.00, then increasing in Cycle II to 86.67% with a mean score of 87.33. These findings indicate that the use of straws as a teaching aid was effective in improving students’ mathematics learning outcomes. The implication of this study is that concrete teaching aids can be used as an alternative instructional medium to enhance understanding and learning outcomes in elementary school mathematics.